Financial sector regulation on the agenda of economic Policy reforms - K. V. Krinichansky; B. B. Rubtsov (Финансы: теория и практика, 2022)
The aim of the research is to identify trends that set the agenda of the structural reforms of OECD countries, as well as of the organization’s partner countries, in the context of the place of financial sector reforms in it.The authors apply the following methods: content-analysis of sources, monitoring of directions and instruments of economic policy in the financial sector, analysis of approaches used by international organizations in order to determine reform priorities (benchmarking), and decomposition of the components of the financial sector reform agenda. The paper shows that the agenda of financial liberalization, formulated in the 1970s, is mostly exhausted, although a certain gap remains between countries with developed and emerging markets in terms of the financial liberalization index. Financial regulatory reforms focused on the goal of building a more resilient global financial system, formulated in the aftermath of the 2007–2009 crisis, are affecting all countries and are also ending. Reforms are now coming to the fore, focusing on areas of the structural transformation agenda such as inclusive growth and an environmental perspective.The paper concludes that the main components of financial reforms in an inclusive context are financial inclusion, financial and digital literacy. In terms of the environmental agenda, the countries are focusing on the tasks of directing financial resources to the implementation of the UN sustainable development goals, introducing ESG investment principles for financial institutions, and developing and implementing principles for issuing green financial instruments.